Μαθηματική προσομοίωση υδροδυναμικών και μορφολογικών διεργασιών στην παραλία Κατερίνης - Μαρμαρά, Δήμητρα (2015)
Μαθηματική προσομοίωση υδροδυναμικών και μορφολογικών διεργασιών στην παραλία Κατερίνης.